Pengaruh Kebiasaan Konsumsi Sayur, Buah dan Perokok Pasif terhadap Kapasitas Antioksidan Total Ibu Hamil - Nadimin Nadimin (Media Kesehatan Masyarakat Indonesia, 2018)
The availability of antioxidants during pregnancy were decreases with increasing of gestational ageand influenced by environmental factors such as exposure to cigarette smoke and consumption habits of vegetablesand fruits. A cross sectional study with pregnant mothers (20-26 months pregnant) non-anemia as many as70 people selected by purposive sampling. Total Antioxidant Capacity (KAT) was measured using Elisa method(enzyme-liked immunosorbent assay), vegetable and fruit consumption habits collected with Food FrequencyQuestionaire (FFQ) and smoking habits using interviews. The results showed around 37,1% of pregnant womenwere passive smokers and rarely consume vegetables and fruits (>60,0%). The mean KAT of pregnant womenreached 2,73±1,48 mmol/l. KAT of passive smokers are significantly lower than non-passive smokers (p=0,038).In General pregnant women who often consume vegetables and fruits have a higher KAT. However, a higher KATwas significantly found in pregnant women who frequently consumed green mustard greens (p=0,049), green beanleaves (p=0,002), apples (p=0,007) and papaya (p=0,029). Exposure to cigarette smoke and less consumption ofvegetables and fruits have lower KAT in pregnant women. Pregnant women should increase consumption of vegetablesand fruits and avoid exposure to cigarette smoke.